Bioactive coatings on porous titanium for biomedical applications - Dominguez-Trujillo, C.; Ternero, F.; Rodriguez-Ortiz, J. A.; Heise, Svenja; Boccaccini, Aldo R.; Lebrato, Julian; Torres, Y. (Surface & Coatings Technology, 2018)
Keywords: Hydroxyapatite; In vitro bioactivity; Bioactive glass coating; Stress-shielding; Osseointegration; Porous titanium

Bioactive coatings on porous titanium for biomedical applications - Dominguez-Trujillo, C.; Ternero, F.; Rodriguez-Ortiz, J. A.; Heise, Svenja; Boccaccini, Aldo R.; Lebrato, Julian; Torres, Y. (Surface & Coatings Technology, 2018)
Keywords: Hydroxyapatite; In vitro bioactivity; Bioactive glass coating; Stress-shielding; Osseointegration; Porous titanium

Bioactive Glass Containing Coatings by Electrophoretic Deposition: Development and Applications - Heise, Svenja; Ramos Rivera, Laura; Boccaccini, Aldo R. (Biomedical, Therapeutic and Clinical Applications of Bioactive Glasses, 2018)

Biodegradable nanostructures: Degradation process and biocompatibility of iron oxide nanostructured arrays - Yang, Yuyun; Zhou, Juncen; Detsch, Rainer; Taccardi, Nicola; Heise, Svenja; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Materials Science and Engineering C, 2018)

Chitosan/bioactive glass coatings as a protective layer against corrosion of nanocrystalline titanium under simulated inflammation - Sotniczuk, Agata; Heise, Svenja; Topolski, Krzysztof; Garbacz, Halina; Boccaccini, Aldo R. (Materials Letters, 2020)
Hydrogen peroxide (H2O2), which is produced during inflammation directly after the insertion of an implant, accelerates the corrosion process of Ti-based materials such as nanocrystalline bulk titanium. For this reason, there is a need to provide additional corrosion protection in the initial period following implantation. Coatings based on chitosan/bioactive glass were obtained by electrophoretic deposition (EPD) on nanocrystalline Ti. Results indicated that homogeneous, crack-free composite chitosan/bioactive glass EPD coatings effectively increased the resistance of nanocrystalline titanium to dissolution induced by H2O2.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Biomaterials; Corrosion; Electrodeposition; Metals and alloys

Developing surface pre-treatments for electrophoretic deposition of biofunctional chitosan-bioactive glass coatings on a WE43 magnesium alloy - Höhlinger, Michael; Heise, Svenja; Wagener, Victoria; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Applied Surface Science, 2017)
The use of Mg alloys as biodegradable implants requires optimizing the surface performance. A high number of surface modification and coating approaches have been previously explored, for instance to make magnesium and its alloys more corrosion resistant. The current study focuses on developing surface pre-treatments as a corrosion protection and primer for further surface modifications by electrophoretic deposition (EPD) of bioadaptive chitosan-bioactive glass coatings. For this, different surface treatments were tested on a WE43 Mg alloy. These treatments include immersion in Dulbecco’s Modified Eagle’s Medium (DMEM), a calcium phosphate treatment, immersion in hydrofluoric acid, and a hydrothermal procedure in NaOH. The resulting coatings were analyzed in view of the surface morphology and composition by SEM/EDX, as well as in view of their short-term corrosion protection ability by electrochemistry. Finally, the suitability of the different pre-treatments as an interfacial protection layer for subsequent EPD of a chitosan/bioactive glass-coating was explored.
Keywords: Pre-treatment; WE43; EPD; Chitosan; Bioactive glass; Corrosion

Development of advanced chitosan-based biodegradable coatings for Mg alloys with potential applications in orthopedic implants - Heise, Svenja (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)

Electrophoretic deposition and characterization of chitosan/bioactive glass composite coatings on Mg alloy substrates - Heise, Svenja; Höhlinger, Michael; Torres Hernández, Yadir; Pavón Palacio, Juan José; Rodriquez Ortiz, Jose Antonio; Wagener, Victoria; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Electrochimica Acta, 2017)
Electrophoretic deposition of chitosan-bioactive glass (45S5 composition) composite coatings on magnesium alloy (WE43) substrates was investigated. Two types of substrates were considered, one was the bare, non-pre-treated substrate, while the other one had been treated in Dulbecco’s Modified Eagle Medium (DMEM). The protective effect of the coatings (of 2 mm in thickness) against corrosion was tested using electrochemical impedance spectroscopy and the coatings’ bioactive behaviour was determined in simulated body fluid. A tribo-mechanical characterization of the coatings was performed. Overall, results confirmed the importance of pre-treating the substrate to corrosion protective chitosan- bioactive glass coatings on WE43 alloy
Keywords: Electrophoretic deposition; magnesium alloys; corrosion; chitosan; bioactive glass; coatings

Electrophoretic Deposition of Bioadaptive Drug Delivery Coatings on Magnesium Alloy for Bone Repair - Qi, Hongfei; Heise, Svenja; Zhou, Juncen; Schuhladen, Katharina; Yang, Yuyun; Cui, Ning; Dong, Rongxin; Virtanen, Sannakaisa; Chen, Qiang; Boccaccini, Aldo R.; Lu, Tingli (ACS Applied Materials and Interfaces, 2019)
Biodegradable polymer coatings on magnesium alloys are attractive, as they can provide corrosion resistance as well as additional functions for biomedical applications, e.g., drug delivery. A gelatin nanospheres/chitosan (GNs/CTS) composite coating on WE43 substrate was fabricated by electrophoretic deposition with simvastatin (SIM) loaded into the GNs. Apart from a sustained drug release over 28 days, an anticorrosion behavior of the coated WE43 substrates was confirmed by electrochemical tests. Both the degradation and corrosion rates of the coated substrate were significantly minimized in contrast to bare WE43. The cytocompatibility of the coated samples was analyzed both quantitatively and qualitatively. Additionally, the osteogenic differentiation of MC3T3El cells on SIM-containing coatings was assessed by measuring the expression of osteogenic genes and related proteins, alkaline phosphatase (ALP) activity, and extracellular matrix mineralization, showing that the SIM-loaded composite coating could upregulate the expression of osteogenic genes and related proteins, promote ALP activity, and enhance extracellular matrix mineralization. In summary, the SIM-loaded GNs/CTS composite coatings were able to enhance the corrosion resistance of the WE43 substrate and promote osteogenic activity, thus demonstrating a promising coating system for modifying the surface of magnesium alloys targeted for orthopedic applications.
CRIS-Team WoS Importer:2019-03-20

Electrophoretic deposition of chitosan/bioactive glass/silica coatings on stainless steel and WE43 Mg alloy substrates - Heise, Svenja; Wirth, Tobias; Höhlinger, Michael; Torres Hernández, Yadir; Rodriquez Ortiz, Jose Antonio; Wagener, Victoria; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Surface & Coatings Technology, 2018)
Keywords: Bioactive glass/silica; Chitosan; Magnesium alloy; Stainless steel; Coatings; Electrophoretic deposition

Electrophoretic deposition of gelatine nanoparticle/chitosan coatings - Heise, Svenja; Forster, Carola; Heer, Svenja; Qi, Hongfei; Zhou, Juncen; Virtanen, Sannakaisa; Lu, Tingli; Boccaccini, Aldo R. (Electrochimica Acta, 2019)
In this study, a biomedical coating system consisting of gelatin and chitosan with potential drug-delivery capability has been developed by electrophoretic deposition (EPD). As substrate material, stainless steel was used. To ensure proper coating bonding to the substrate, chitosan was used as a polymer matrix in which gelatin nanospheres were embedded. The amount of ethanol in the EPD suspension was optimized (reduced) in order to allow for the incorporation of ethanol-sensitive growth factors into the coating. Gelatin microspheres were prepared with two different cross-linking degrees (low and high) to tailor their degradation kinetics. The suspension stability was analysed by zeta potential measurements and the coating mechanism was investigated. EPD was confirmed to enable the co-deposition of chitosan and gelatin nanospheres in a single coating step. The achieved layers were analysed regarding their microstructure (light and scanning electron microscopy), wettability, composition and degradation behavior. (C) 2019 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-05-03

Influence of proteins on the corrosion behavior of a chitosan-bioactive glass coated magnesium alloy - Höhlinger, Michael; Christa, Daniel; Zimmermann, Victoria; Heise, Svenja; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Materials Science and Engineering C, 2019)
The current study explored the degradation behavior of a WE43 Mg alloy during immersion tests in Dulbecco's Modified Eagle's Medium (DMEM) for 3d and 7d, for a bare alloy surface as well as for samples with surface pretreatment, and finally for samples coated with chitosan-bioactive glass. The immersion tests were conducted with and without addition of serum, to study the influence of proteins on the degradation process. Mass-loss was measured to determine the corrosion rate after 3d and 7d of immersion. The samples were analyzed by SEM with respect to their surface morphology and the chemical composition was screened by high-resolution XPS. The results demonstrate not only a significant, time-dependent influence of serum addition on the corrosion behavior of the materials studied, but noteworthy is that depending on the sample type, proteins in solution were observed to either accelerate or inhibit corrosion. These results are discussed in correlation to observed changes in surface chemistry taking place upon immersion in the absence and presence of proteins.
CRIS-Team WoS Importer:2019-06-04

Tackling Mg alloy corrosion by natural polymer coatings - A review - Heise, Svenja; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2016)
The field of protective coatings for magnesium and its alloys (e.g., AZ31) using natural polymers is reviewed. Polymers utilized are broadly divided into polysaccharides and proteins. For both polymer classes examples are given focusing on coating processing and characterization. Several analysing methods reported in literature are summarized highlighting the different characterization approaches applied in different studies, which makes difficult a direct comparison of the outcomes. In most cases, the protective behavior of coatings was determined using electrochemical impedance spectroscopy or by assessing hydrogen evolution in different fluids. Mechanical tests and in vitro cell culture studies have been also carried out on selected coating systems. Overall, the results show the possibility of applying protective coat- ings based on natural polymers on magnesium and its alloys, however, in vivo investigations are scarce so that long-term results in relevant conditions are not yet available. A compar- ison with the use of synthetic polymers is presented and cur- rent challenges and areas for future research are discussed, highlighting the need for further investigations in the field, which should enable broadening the applications of Mg and Mg alloys in medicine.
Keywords: magnesium alloys; biodegradable material; natural polymers; coatings; corrosion resistance

Taguchi Design of Experiments approach to determine process parameter for the electrophoretic deposition of chitosan/bioactive glass on Mg alloy substrates - Heise, Svenja; Virtanen, Sannakaisa; Boccaccini, Aldo R. (ECS Transactions, 2018)
Bioactive glass/chitosan composite coatings were successfully deposited on a Mg alloy (WE43) by electrophoretic deposition (EPD). A Taguchi Design of Experiments approach was employed to optimize the deposition parameters (time and voltage) and the roughness of the sample, which influence the final morphology of the coating. The surface coverage was taken as target function and evaluated with a point counting method. The optimized parameters fulfil the prediction; however, a second coating layer is still needed due to the corrosive nature of the magnesium substrate. This second layer is needed to close all pores, giving a defect free coating surface.